Genetica de la prolificidad en el cerdo iberico: Revision de metodologias y resultados - Dobao, M.T.=700 1 Rodriguez, J.; Silio, L.; Toro, M.A.
(En, Es)
Ilus., 46 ref.
Keywords: CERDO; GENETICA; PROLIFICIDAD; CONSANGUINIDAD; CRUZAMIENTO; SELECCION; ESPAÑA; INVESTIGACION AGRARIA